Analisis Kesalahan Gaya Berbahasa Pada Sosial Media Instagram Dalam Caption dan komentar - Ima Nur Rezgina (CV. Alim's Publishing, 2023)
This study aims to describe the forms of language errors found on Instagram social media. Analysis of language errors is a method or work step that is commonly used by esearchers or language teachers to collect data, identify errors, explain errors, classify errors and valuate the seriousness of language errors. The use of language on social media on Instagram as a means of daily communication, one of which is to comment and text. Various languages are used in communication, including Indonesian, regional languages, various languages, and foreign languages. This study aims to describe the form of misuse of Indonesian on Instagram and to describe the forms of misunderstanding of the use of Indonesian on Instagram. This research method uses qualitative descriptive because in this study the researcher identifies language errors that are on social media, especially on Instagram. The results showed the ineffectiveness of language users carried out by Instagram social media users in the form of using Indonesian, (1) spelling errors (2) use of diction (3) grammatical structural errors. There are also forms of misunderstanding in the use of Indonesian on Instagram (1) variations of Indonesian and English (2) variations of Indonesian with slang, English, local languages.